Financial Literacy in Facing Technology and Economic Instability - Octavianus, Joshua; Taufan, Yuniarko Ali (LifeSciFi, 2024)
This research examines the relevance of financial literacy for the younger generation in the context of heading towards Indonesia’s golden generation 2045. Focusing on the financial challenges faced by millennials and Generation Z, this study aims to explore the influence of technology, digitalization, and social media on their financial management, as well as the impact of economic instability on financial planning. Through a quantitative survey of 50 respondents, this research measures variables such as financial education, the influence of social media, and economic uncertainty, as well as financial behavior and financial well-being. Analysis using Multiple Linear Regression shows that financial literacy plays an important role in shaping adaptive and wise financial behavior, avoiding consumerism, and considering financial future. These findings suggest that improving financial literacy can help the younger generation in facing financial challenges, with recommendations for more comprehensive integration of financial education in the curriculum and the use of technology in effective financial management. This study provides insights into effective financial management strategies and public policies that can support the younger generation in managing their finances.